Assessment of the Rocky Mountain National Park Breeding Bird Monitoring Program - Meyer, Kristen, author (Colorado State University. Libraries, 2008)
The Rocky Mountain Bird Observatory collected 10 years of data throughout the state of Colorado using similar distance-sampling methods to those employed by the Park and will continue these monitoring efforts into the future. In order to assess if RMBO data could be used for management planning in the Park, annual densities were estimated for each year from 2000 to 2006 for the Park and compared to breeding bird data collected for the state of Colorado by the Rocky Mountain Bird Observatory. Trends in annual density estimates were not evident in the RMNP data for all of the species because the confidence intervals overlapped across many of the years. There were also no clear differences between the RMNP and RMBO data for most species in most habitat types due to overlapping confidence intervals between the two datasets. Four species in high-elevation riparian habitat showed different densities in the park data than the statewide data, while seven species in ponderosa pine habitat had larger densities in the RMNP data than the statewide data. Although a distinct comparison between the two datasets was inconclusive, the results of this study provided information to make future monitoring recommendations for optimum time intervals, targeting indicator species, increasing sample sizes, and improving data quality.
Keywords: Rocky Mountain National Park; RMNP; Rocky Mountain Bird Observatory; RMBO; breeding bird data; Birds -- Colorado -- Statistics; Rocky Mountain National Park (Colo.)